PENGEMBANGAN HANDOUT BERMUATAN KECERDASAN KOMPREHENSIF UNTUK MATERI LAJU REAKSI PADA KELAS XI SMA - Fatma '; Betty Holiwarni; Susilawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The quality education wold be realized with the procurement of teaching material in handout form in accordance with 2013 curriculum. This handout is should make a contain of spiritual intelligence value, social and emotional intelligence, intellectual intelligence and skil intelligence. However, the handout does not yet exist. The solution for that, was created a handout that containing comprehensive intelligence, and finally the author make a research that have to make a valid comprehensive intelligence handout. The research included into the research and development type. The research object is comprehensive intelligence handout. Data collection instrument that used the validation sheet. Data collection metode according make a validation learning equipment to validator. The validation result then used to develop to get result of analysis data. Data analysis methode according descriptive analysis methode. Basicly on data analysis it can be argued that the develop handout already containing spiritual intelligence, social emotional intelligence, intellectual intelligence,and skill intelligence as suitable as reaction rate material. This handout had been throught a validation process and otherwise have the egibility of content component, language, presentation and graphic with consecutive percentage on 96.88%, 95%, 93,75, and 96,25% than indicates the handout in valid category and feasible to be tested.Keyword : Handout, comprehensive intelligence, reaction rate